A Conceptual Study on Rogaha Sarvepi Mandagnau (Mandagni is the Root Cause of all Diseases) (AYUSHDHARA, 2024)
“Swasthasya swasthya rakshanam, Aturasya vikara prasamanam ca” is main goal of Ayurveda which means to protect and maintain Swasthya (wellness) of a healthy person and to treat diseases of diseased. Ayurveda given many fundamental concepts like, Tridosha, Sroatasa, Agni, Dhatu, Mala, Ojasa etc. Among them Agni is regarded as one of the fundamental concepts that controls how the human body functions physiologically and responsible for maintaining good health. Agni controls the genesis and dissolution of the universe as well as metabolism and catabolism of an organism. It is described by Acarya that Agni is responsible for strength and life exists due to proper functioning of Agni. We find that almost all diseases in the Ayurveda are an outcome of Mandagni (impaired digestion). Mandagni is the state of Agni which cannot digest even little quantity of food in the scheduled time. The aim of this article is to provide light on the physiological and aspects of Agni, as well as its function.